Estate division: Equal sharing as choice, social norm, and legal requirement - Oscar Erixson; Henry Ohlsson (Research Institute of Industrial Economics (IFN), 2014)
The objective of this essay is to study to what extent parents divide their estates unequally between their children and the determinants of this decision. We use a new dataset based on the estate reports for almost 70,000 Swedish widows, widowers, divorcees and unmarried individuals who died with positive estates and at least two children. Unequal sharing is unusual; depending on definitions only 2-12 percent of the estates are unequally divided. Previous studies for other countries, particularly from the US, find that around 20-40 percent of parents divide their estates unequally. We argue that the relatively low frequency of unequal sharing in Sweden might be explained by contextual factors such as the inheritance law, the transfer tax system, the income distribution, and the welfare state. We also estimate models with family fixed effects to study how the characteristics of children to parents who choose unequal division affect the size of the transfer. The empirical estimates show that bequests are not used to compensate for income differences between children, suggesting that bequests are not guided by altruistic motives. Children who are likely to have provided services to the parent receive more than their siblings however. This suggests that, at least some bequests are guided by exchange motives.
Keywords: C81; D10; D31; D91; H24; 330; estate division; wills; equal sharing; bequests motives; inheritances